ACTR-50. PRESERVATION OF NEUROCOGNITIVE FUNCTION & PATIENT-REPORTED SYMPTOMS WITH HIPPOCAMPAL AVOIDANCE (HA) DURING WHOLE-BRAIN RADIOTHERAPY (WBRT) FOR BRAIN METASTASES: LONG-TERM RESULTS OF NRG ONCOLOGY CC001. (11th November 2019) - Armstrong, Terri; Deshmukh, Snehal; Brown, Paul; Gondi, Vinai; Benzinger, Tammy; Gilbert, Mark; Tome, Wolfgang; Wefel, Jeffrey; Bruner, Deborah; Roberge, David; Kundapur, Vijayananda; Devisetty, Kiran; et al.
Abstract: BACKGROUND: NRG-CC001 sought to evaluate the neuro-protective effects of avoiding the peri-hippocampal stem cell niche using intensity-modulated radiotherapy during WBRT. METHODS: Patients with brain metastasis were stratified by RPA class and prior radiosurgery/surgery and randomized to WBRT+M or HA-WBRT+ Memantine (M) (30Gy in 10 fractions). Standardized NCF tests and the M.D. Anderson Symptom Inventory Brain Tumor (MDASI-BT) were obtained at baseline, 2, 4, 6, and 12 months (mos). The primary endpoint was NCF failure defined using the reliable change index. Pre-specified secondary endpoints included patient-reported symptoms using the MDASI-BT. Time to NCF was reported as cumulative incidence (with death without NCF failure as a competing risk); between-arms differences were tested using Gray's test. Deterioration at discrete time-points were tested using chi-square tests. MDASI-BT symptom burden, interference, and cognitive and neurologic burden were analyzed using mixed effects models and t-tests within the model using Hochberg's multiplicity adjustment. RESULTS: A total of 518 patients were randomized from 7/2016 to 3/2018. Median follow-up for alive patients was 12.1 mos, with no difference between arms in terms of toxicity, overall survival or intracranial progression-free survival. HA-WBRT+M was associated with lower risk of NCF failure (adjusted HR=0.739, 95% CI: 0.577–0.945, p=0.0.016), with differences first noted at 4 mos in Trail Making Test Part-B (23.3% vs. 40.4% deteriorated, p=0.012). Age did not dilute treatment effect. HA-WBRT+M was associated with reduced cognitive symptom burden in an imputed model (estimate=-0.29, p=0.0425), and also reduced overall symptom burden (p< 0.0001) and interference (p< 0.0016) at 6 mos. CONCLUSIONS: The addition of HA to WBRT+M preserved NCF and reduced patient reported cognitive symptom burden, overall symptom burden and symptom interference and should be considered standard of care for any patient fit enough to have WBRT. Supported by grants UG1CA189867 (NCORP), U10CA180868 (NRG Oncology Operations), DCP from the National Cancer Institute.